(untitled) (Medical Forum Monthly, 2024)
Objective: To study the incidence of gestational diabetes and viral hepatitis in pregnant womenpresnting in Islam Central Hospital Sialkot Study Design: Cross sectional study based on patients attending Islam Central Hospital, Sialkot Place and Duration of study: This study was carried out at Islam CentralHospital, Sialkot from 1st January 2012 to 30 November 2013. Material & methods: Two hundred pregnant women were selected randomly attending Islam CentralHospital, Sialkot. The data was collected on proforma. The written informed consent was obtained on the consent form and permission was taken from the hospital committees. Blood samples were taken for diagnoses of hepatitis and second sample was taken for fasting blood glucose and then 75gm glucose in one glass of water was given to the patients. After 2 hours, another plasma glucose test was taken. Gestational diabetes was diagnosed on the basis of fasting plasma glucose level>126mg/dl, 2 hours post prandial plasma glucose level >199.8mg/dl and hepatitis was diagnosed by its kits. Results: The age variation of pregnant women included in this study was as follows. 20 patients (10%) were of age 16-20 years, 102(51%) of age 21-30 years, 54(27%) of age 31-40 years and 24(12%) of age 41-50 years. 70 patients(35%) included in this study had undergone major surgery e.g., caesarean section while 130(65%) had not undergone any major surgery. 54(27%) pregnant women had history of blood transfusion and 146(73%) pregnant women had no history of blood transfusion. 158(79%) of the pregnant women had undergone minor procedure e.g., tooth extraction or ear piercing and 42(21%) had not undergone any minor procedure. 30(15%) of the pregnant women had history of miscarriage conducted by Dai and 170(85%) had no history of dai handling. The incidence of overweight/obesity was 138 (69%) in case of pregnant women and 62(31%) had no evidence of being overweight/obese. The incidence of gestational diabetes was 34(17%) in pregnant women and 166(83%) had no history of gestational diabetes. The incidence of viral hepatitis was 18 (9%) in pregnant women and 182 (91%) had no evidence of viral hepatitis. In this study, out of 9 cases, 3 cases (33.33%) were suffering from hepatitis A, 2 cases (22.22%) from hepatitis B and 4 cases (44.44%) were sufferingfrom hepatitis C. Conclusion: As the hygienic conditions in our country are very poor and dietary habits include eating food containing high carbohydrates and fatty contents so the incidence of metabolic diseases is increasing. The sedentary life style is also becoming common in pregnant women in our country therefore the incidence of gestational diabetes and hepatitis is increasing day by day in pregnant women irrespective of age, occupation, socioeconomic status, residential area and gravidity status.